2013
DOI: 10.4103/2141-9248.113683
|View full text |Cite
|
Sign up to set email alerts
|

Compound odontoma in deciduous dentition

Abstract: Odontomas are benign tumors containing all the components of the odontogenic tissue. Disturbances in tooth eruption are one of the most common complications associated with odontomas. They are generally asymptomatic and are usually seen in second and third decades of life, rarely seen below 10 years of age. Herewith, we report an unusual occurrence of compound odontoma in a 4-year-old child visualized as a swelling of the cortical bone in the anterior maxilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…7 In humans, odontomas usually occur in the second decade, 4 and there are only rare reports of odontomas associated with deciduous teeth. 36,37 The etiopathogenesis of odontomas, either in humans or nonhuman species, is not known. Localized trauma, infection, and genetic predisposition have all been postulated as possible inciting factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 In humans, odontomas usually occur in the second decade, 4 and there are only rare reports of odontomas associated with deciduous teeth. 36,37 The etiopathogenesis of odontomas, either in humans or nonhuman species, is not known. Localized trauma, infection, and genetic predisposition have all been postulated as possible inciting factors.…”
Section: Discussionmentioning
confidence: 99%
“…7 In humans, odontomas usually occur in the second decade, 4 and there are only rare reports of odontomas associated with deciduous teeth. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…Thus, education, life experiences and the economics of a community may impart whether an individual may or may not initiate healthcare seeking behavior [37]. Self-reported use of CAM among the healthcare consumers at a tertiary care center in UAE demonstrates that 70% of the users did not consult any physician, but used it with non-medical information [8]. A review of qualitative and quantitative studies conducted in the US between 1993 and 2002 found the rate of non-disclosure of those using CAM is as high as 77%, and includes reasons such as concerns about a negative response by the practitioners, the belief that the practitioner did not need to know about their CAM use, and the fact that the practitioner did not ask [38].…”
Section: Discussionmentioning
confidence: 99%
“…Complementary and alternative medicine prevalence in some developed countries is between 70% and 80% [4]. Countries throughout the Middle East including Egypt, Jordan and the Arabian Gulf have began incorporating herbal CAM along with conventional medicine into the National Health Services [8]. Major challenges exist in the implementation of traditional, complementary, alternative and herbal medicine as it pertains to regulatory status, efficacy, quality control and safety monitoring [9].…”
Section: Introductionmentioning
confidence: 99%
“…When odontomas are associated with unerupted teeth, orthodontic traction of the impacted tooth almost immediately subsequent to removal of the lesion might be desired. [12] Similarly in the present case surgical removal of odontoma was done. Further the possibility of spontaneous eruption of permanent incisors after removal of odontoma cannot be ruled out; so it was decided to keep the patient under periodic observation for next 12 months, before any active orthodontic intervention.…”
Section: Discussionmentioning
confidence: 99%